2018
DOI: 10.1111/tpj.14108
|View full text |Cite
|
Sign up to set email alerts
|

The cotton XLIM protein (GhXLIM6) is required for fiber development via maintaining dynamic F‐actin cytoskeleton and modulating cellulose biosynthesis

Abstract: N.-N.W. contributed equally to this work.SUMMARY LIM domain proteins are cysteine-rich proteins, and are often considered as actin bundlers and transcription factors in plants. However, the roles of XLIM proteins in plants (especially in cotton) remain unexplored in detail so far. In this study, we identified a cotton XLIM protein (GhXLIM6) that is preferentially expressed in cotton fiber during whole elongation stage and early secondary cell wall (SCW) synthesis stage. The GhXLIM6-silenced transgenic cotton p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…There is a distinct rearrangement of the actin cytoskeleton during transition from fiber elongation to secondary wall deposition (Seagull, 1990; Wang et al, 2010). In line with the cytological observations, a variety of ABP encoding genes have been found to be preferentially expressed in developing fiber cells, such as those encoding actin deploymerizing factors (Wang et al, 2009), profilins (Wang et al, 2005; Wang et al, 2010; Bao et al, 2011), and LIM-domain proteins (Han et al, 2013; Li et al, 2013; Li et al, 2018). Moreover, studies of transgenic cotton suggest that some increases in F-actin abundance are beneficial for fiber quality improvement (Wang et al, 2009; Han et al, 2013), and formation of the higher actin cytoskeleton structure plays a determinant role in the progression of developmental phases of cotton fibers (Wang et al, 2010; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…There is a distinct rearrangement of the actin cytoskeleton during transition from fiber elongation to secondary wall deposition (Seagull, 1990; Wang et al, 2010). In line with the cytological observations, a variety of ABP encoding genes have been found to be preferentially expressed in developing fiber cells, such as those encoding actin deploymerizing factors (Wang et al, 2009), profilins (Wang et al, 2005; Wang et al, 2010; Bao et al, 2011), and LIM-domain proteins (Han et al, 2013; Li et al, 2013; Li et al, 2018). Moreover, studies of transgenic cotton suggest that some increases in F-actin abundance are beneficial for fiber quality improvement (Wang et al, 2009; Han et al, 2013), and formation of the higher actin cytoskeleton structure plays a determinant role in the progression of developmental phases of cotton fibers (Wang et al, 2010; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…This kind of integrated strategy efficiently isolated and validated several key genes with important functions. For instance, GhARF2, GhARF18 [52], GhXLIM6 [53], GhFSN1 [54], GhJAZ2 [55], GhFAnnxA [56], GhPAG1 [57], GhCETS [58], GhHSP24.7 [59,60], GhAAI66 [61], GhDsPTP3a [62], GhERF38 [63], GhABF2 [64], CRR1 [65], GhERF38 [63], GbSOBIR1 [66], and GhCPK33 [67], as well as other genes necessary for fiber development, growth, germination, gossypol, flowering, and resistance to abiotic and biotic stresses and diseases have been described.…”
Section: Integrated Strategies For Gene Cloningmentioning
confidence: 99%
“…Cotton fiber is developed from the differentiation of a single ectodermic epidermal cell, and the fiber formation process can be divided into four distinct but partially overlapping periods: initiation, elongation (primary wall formation), secondary wall thickening, and dehydration maturity [19]. Many methods, including QTL identification [20][21][22], GWAS analysis [23][24][25][26], and functional gene identification [27][28][29], have been used to tackle the problems of fiber development and fiber quality formation. Studies have revealed that fiber development is a very complex process, with a large number of metabolic pathways providing material support, and thousands of specific genes being involved in expression regulation.…”
mentioning
confidence: 99%